Mengembangkan praktik moderasi beragama melalui hospitalitas berbasis iman: Sebuah tawaran model menggereja pada pembacaan Ibrani 13:2 - Saetban, Sem; Baun, Soleman; Kase, Simon (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2024)
Amidst Indonesia's pluralistic yet friction-prone religious landscape, the idea of ​​religious moderation is crucial. This article presents a theological and practical model for the church to make substantive contributions to this agenda. Building on an exegetical-hermeneutical reading of Hebrews 13:2, this article argues that the practice of hospitality toward